The Research on Strain-Softening Characteristics and Local Fracture Law of Deep Granite Roadway. (22nd June 2020) - Sun, Chuang; Ao, Yunhe; Wang, Laigui
Abstract : The complex mechanical properties of deep surrounding rocks during excavation and unloading have always been a concern in engineering communities. Based on deep roadway engineering, the mechanical properties of granite strain-softening were investigated by laboratory tests. An exponential relationship between granite peak softening modulus and confining pressure was obtained using a nonlinear fitting method. A strain-softening model was developed based on plasticity theory for granite which took into account the nonlinear dilatancy angle and confining pressure. A mathematical model was developed using FLAC 3D as platform. By developing a numerical model for a deep roadway, the local fracture characteristics of deep surrounding rocks under strain-softening conditions were evaluated. It has been found that the postpeak failure of granite had a tendency for brittle-ductile transformation. Under high confining pressure conditions, granite exhibited brittle failure characteristics during the postpeak period, and the postpeak softening modulus was decreased with the increase of confining pressure. From FLAC 3D numerical calculations, it was found that the numerical models of different mesh densities had basically the same characteristic curves of surrounding rocks, which showed that the local cracking phenomenon had little effect on calculation results when the convergence constraint method was applied for the calculation of the stability of supporting structures and surrounding rocks. It was seen from the numerical simulation analyses of surrounding rock local fracture properties in deep roadways that plastic shear strain appeared in the local areas of roadway vault and arch foot, which basically coincided with the damage location and depth of surrounding roadway rocks.